2010
DOI: 10.1086/652158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Different Types of Surgical Gloves Used for Preventing Blood Contact

Abstract: Double gloving or the use of a glove with disinfectant can result in a decrease in the volume of blood transferred. Therefore, the use of either of these gloving systems could help to minimize the risk of bloodborne infections for medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
6
0
3
Order By: Relevance
“…In addition, apart from being exposed during the needlestick injuries, venous blood sampling is always associated with a risk for blood contact and contamination during the procedure. There is evidence showing that this risk is reduced using gloves [45,46]. It has been shown that hand cleansing is the key to the reducing the risk of the infection of the healthcare staff and crosstransmission of antimicrobial resistant pathogens.…”
Section: Samplingmentioning
confidence: 99%
“…In addition, apart from being exposed during the needlestick injuries, venous blood sampling is always associated with a risk for blood contact and contamination during the procedure. There is evidence showing that this risk is reduced using gloves [45,46]. It has been shown that hand cleansing is the key to the reducing the risk of the infection of the healthcare staff and crosstransmission of antimicrobial resistant pathogens.…”
Section: Samplingmentioning
confidence: 99%
“…15.3/100,000 hospital employees, Table 4), awareness for the infection risk and knowledge about infection prevention should be improved [30,31]. Communicating the safety and effectiveness of vaccination will be an important issue in this endeavour [32][33][34] as well as improvements in protective equipment likes gloves or safety devices [35,36].…”
Section: Limitationsmentioning
confidence: 99%
“…We were therefore not only able to accurately detect the smallest leakages when administering insulin, 8 but we were also able to prove the protective function of surgical gloves. 9 This method has now also proven to be suitable for the measurement of potentially infectious blood splashes in very low volumes of blood in the nanoliter range.…”
Section: Discussionmentioning
confidence: 99%